Assessment of satisfaction with quality of stationery long-term social care system: the Stavropol Territory case - E. V. Nemtseva; K. V. Bagmet; E. V. Ivanova; K. A. Samofatova (Вестник университета)
The purpose of the article is to assess satisfaction with quality of long–term stationary social care system for elderly population in the Stavropol Territory, as well as to identify problem areas in its functioning and form a set of management solutions to eliminate them. The paper analyzes the results of a sociological study having been conducted from January to July 2022. It has confirmed a high level of satisfaction with quality of the system by the elderly as well as employees of the pilot institutions of the region. The sample size of the study is 440 respondents. Such research methods as analytical method, secondary analysis, anonymous written survey, statistical methods of data processing, and graphical methods of presenting the data obtained have been used.